IMPLEMENTATION OF PUBLIC POLICY IN IMPROVING PUBLIC WELFARE - Loso Judijanto; Jackson Yumame; Melyana R Pugu (CV. Adiba Aisha Amira, 2024)
The study aims to examine how implementation of public policy can affect the well-being of the public. Through an in-depth analysis of the literature, the study identifies key factors that play a role in the success of public policies such as education, health, employment, housing, and social protection. With a focus on the developing-country context, the study seeks to provide new insights into how public policies can be effectively implemented to improve public well-being. From the analysis of the literature, the study found that the success of public policy implementation in improving the well-being of communities depends mainly on several key factors: (1) inclusive and evidence-based policy design; (2) availability of adequate resources; (3) good inter-agency coordination and collaboration; (4) policy adaptation to local contexts; and (5) active participation of the community. Furthermore, the main challenges emerging relate to resource constraints, resistance from stakeholders, and changing political-economic conditions. The study proposes several strategies to improve policy implementation effectiveness, including enhancing institutional capacity, using participatory approaches in policy formulation and implementation, and increasing transparency and accountability in decision-making processes. This research reaffirms the importance of a comprehensive and multidisciplinary approach in designing and implementing effective public policies to enhance public well-being.